Penerapan Metode Demonstrasi Menggunakan Benda Konkret Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VI Semester II SD Negeri 1 Seraya - I Nyoman Mudiana (Cetta: Jurnal Ilmu Pendidikan, 2019)
To improve students' mathematics learning outcomes, one of them needs to be improved on the quality of mathematics learning in elementary school. This study aims to improve student learning outcomes from cognitive aspects. The subjects of this class action research are Class VI Semester II students at SD Negeri 1 Seraya with a total of 21 people. Whereas the object of research is student learning outcomes from cognitive aspects. Learning outcomes are collected by a description test. The data obtained were analyzed using descriptive qualitative analysis techniques. From the results of data processing obtained the first cycle the average student learning outcomes are 64.3, 64% absorptive capacity and 62% learning completeness which are classified as incomplete. In the second cycle student learning outcomes amounted to 86.9, absorption of 87% and 95% learning completeness classified as complete. Learning completeness in learning is achieved when students have reached the demands of curriculum, namely the average grade value of at least 65, 65% absorption power and 85% learning completeness. Based on data analysis, it can be concluded that the use of concrete media can improve learning outcomes from cognitive aspects in mathematics. This is evidenced by the increasing learning outcomes of Class VI students in Semester II at SD Negeri 1 Seraya while with an increase in absorption from the pre-cycle of 55%, the first cycle was 64% to 87% in the second cycle. Similarly, student learning completeness increased from the initial state of 33%, to 62% in the first cycle to reach 95% in the second cycle. From the results of the Classroom Action Research, researchers will continue similar activities to improve the quality of learning in schools.